The effect of political connection and effectiveness of audit committee on audit fee - Fitri Nurjanah; Erina Sudaryati (Universitas Hayam Wuruk Perbanas, 2019)
This study analyzes the effect of political connection and effectiveness of audit committee on audit fee. This study uses the sample of non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. They were take using a purposive sampling method. The total number of companies is 444 companies. The data were analyzed using SPSS 20 and the hypothesis testing was done using linear regression with a significance level of 5%. The F test indicates that the research model is stable and significant. The value of R square is 38.4%, indicating that there are other variables that can affect the model by 61.6%. The results of this study show that political connection has a significant positive effect on audit fee and the effectiveness of audit committee also has a significant positive effect on audit fee because audit committee wants a higher audit quality from the auditor.